Realistic and Theoretical 3D Modelling of the Sedimentation, Burial, Thermal and Tectonic History of the Gippsland Rift Basin - Yang, Xuemei (Curtin University, 2022)
The project investigated the sedimentary, burial, thermal and tectonic history of the Gippsland rift basin, using a realistic 3D structural and stratigraphic model of the basin to constrain theoretical deterministic models, including 3D forward palaeo-landscape models and 3D burial and thermal models of the entire Gippsland Basin. An efficient Experimental Design approach was used to guide the scenario set-up for the numerical simulation software, process the palaeo-landscape results, and identify the important controlling variables.